Olympic lifting and plyometrics in youth athletes - Dodd, K. D.; Newans, T. J. (Journal of Australian Strength and Conditioning, 2017)
The purpose of this review was to gain a greater understanding of the ground reaction forces (GRF) involved in Olympic weightlifting (OL) and plyometrics, and OL`s impact on tissue adaptation in youth athletes. The review also aimed to devise a process of combining plyometric and OL in a safe and beneficial manner to the athlete`s development. 36 articles and 2 books were used to review the current literature on OL and plyometrics. After conducting a review of current literature, it was found that OL GRFs increased as displacement of the load to be lifted decreased, whilst plyometric GRFs increased as the displacement of the jump height increased. OL elicited beneficial adaptations to bone and muscle with speculative adaptations to tendon and ligament. When used in conjunction, OL and plyometrics could result in a greater power performance by targeting both aspects of the power equation (power = force x velocity). This review concludes that OL should be utilised during the youth developmental years to enhance bone and muscle adaptations. OL should also be used in conjunction with plyometric exercises to target the force and velocity components of power.